2016
DOI: 10.1159/000441954
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response Syndrome Following Percutaneous Nephrolithotomy: Assessment of Risk Factors and Their Impact on Patient Outcomes

Abstract: Objectives: To identify perioperative risk factors for postoperative systemic inflammatory response syndrome (SIRS) and suggest possible modifications to reduce morbidity. Material and Methods: We prospectively analysed perioperative data such as history of pervious stone surgery, number and configuration of stones, presence of stent or nephrostomy, any previous positive urine culture, intraoperative renal pelvic urine and stone culture, aspiration of turbid urine on initial puncture, number of tracts required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 20 publications
(26 reference statements)
1
31
0
Order By: Relevance
“…However, the application of ESWL in obese patients is limited because of the skin-tokidney distance and the burden of the existence of large stones; similarly, the application of RIRS in obese patients with stones >2 cm is limited [7] . PCNL is the gold standard first-line treatment in the management of renal stones larger than 2 cm [19] . Obesity is generally speculated to increase the morbidity of surgery, primarily because of wound, pulmonary, and cardiac complications [20] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of ESWL in obese patients is limited because of the skin-tokidney distance and the burden of the existence of large stones; similarly, the application of RIRS in obese patients with stones >2 cm is limited [7] . PCNL is the gold standard first-line treatment in the management of renal stones larger than 2 cm [19] . Obesity is generally speculated to increase the morbidity of surgery, primarily because of wound, pulmonary, and cardiac complications [20] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that urosepsis after MPCNL might lead to high mortality especially among patients with complex stones [15]. It is of great importance for clinicians to detect postoperative systemic inflammatory response syndrome (SIRS) and prevent SIRS from progressing to urosepsis [16]. Previous studies have found a significant association between preoperative UTI and urosepsis after endoscopic surgeries for upper urinary tract stones [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional survey of the prevalence of urinary calculi in China showed that the prevalence rate was 6.50% (1). Percutaneous nephrolithotomy (PCNL) has been widely used for the treatment of renal stones (2), and it has also become the standard of care for large (>2 cm) renal stones (3). PCNL has become one of the main methods used to treat renal and upper ureteral calculi in recent years.…”
Section: Introductionmentioning
confidence: 99%